COMPARATIVE ANALYSIS OF THE IMPLEMENTATION OF AGRARIAN LAW IN AREAS - Andi Fahratul Sriwani; Faradila Ramadani; Nur Paridah Mey Yulia; Wirdatul Jannah; Asnawi Mubarok (PT. Antis International Publisher, 2024)
The study aims to analyze the comparison of the implementation of agricultural law in different countries. The discussion of land is important in the context of the development of a country because land is a valuable asset and a source of life for the people. Nonetheless, the implementation of agricultural law often faces challenges that are obstacles to achieving agricultural governance effectively and fairly. This study employs a comparative research method. We collect the data from a variety of relevant sources, including legislation, policies, and related literature. We carried out the analysis to compare the differences and similarities in the implementation of agricultural law on land in the countries involved in the case studies. We expect the results of this research to provide a deeper understanding of the implementation of agricultural law on land in various contexts and countries. This study will also discuss the importance of adapting agricultural laws to the needs and socio-economic realities of local communities. The research aims to guide policymakers in crafting and executing more equitable and effective agricultural policies for farm management.